Roman military diplomas 1954-1977 - Roxan, Margaret M., author.
1 online resource (120 pages).
Keywords: This volume publishes records 82 diplomas or fragments which provide vital evidence for the Roman military and legal world. It is the first volume of a set of four created by Roxan, the world's expert on this subject.